Rotationally Driven Ultraviolet Emission of Red Giant Stars. II. Metallicity, Activity, Binarity, and Subsubgiants - Don Dixon; Keivan G. Stassun; Robert D. Mathieu; Jamie Tayar; Lyra Cao (The Astronomical Journal)
Red-giant-branch (RGB) stars are overwhelmingly observed to rotate very slowly compared to main-sequence stars, but a few percent of them show rapid rotation and high activity, often as a result of tidal synchonization or other angular momentum transfer events. In this paper we build upon previous work using a sample of 7286 RGB stars from APOGEE DR17 with measurable rotation. We derive an updated NUV excess versus $v\sin i$ rotation–activity relation that is consistent with our previous published version, but reduces uncertainty through the inclusion of a linear [M/H] correction term. We find that both single stars and binary stars generally follow our rotation–activity relation, but single stars seemingly saturate at P _rot / $\sin i$  ∼ 10 days while binary stars show no sign of saturation, suggesting they are able to carry substantially stronger magnetic fields. Our analysis reveals subsubgiant stars (SSGs) to be the most active giant binaries, with rotation synchronized to orbits with periods ≲20 days. Given their unusually high level of activity compared to other short-period synchronized giants, we suspect the SSGs are most commonly overactive RS CVn stars. Using estimates of critical rotation we identify a handful giants rotating near breakup and determine tidal spin up to this level of rotation is highly unlikely and instead suggest planetary engulfment or stellar mergers in a fashion generally proposed for FK Comae stars.